Stabilization vs. destabilization of G-quadruplex superstructures: the role of the porphyrin derivative having spermine arms. Issue 26 (26th June 2017) - D'Urso, A.; Randazzo, R.; Rizzo, V.; Gangemi, C. M. A.; Romanucci, V.; Zarrelli, A.; Tomaselli, G.; Milardi, D.; Borbone, N.; Purrello, R.; Piccialli, G.; Di Fabio, G.; et al.
Abstract : Induction of different complexes including GQ superstructures, depending on the method used (titration vs. single addition) to add the spermine porphyrin derivative. Abstract : The interaction of the porphyrin derivative H2 TCPPSpm4, having spermine pendants in the four meso positions, with the G-quadruplex (GQ) structure formed by the DNA aptamer TGGGAG has been investigated by means of UV, electronic circular dichroism and PAGE studies. The results reported here demonstrate that the porphyrin derivative is capable of stabilizing or destabilizing the higher-ordered structures of parallel GQs, depending on the method used to reach their relative stoichiometry (titration vs. single addition). Noteworthily, when two equivalents of H2 TCPPSpm4 were mixed directly with one equivalent of the (TGGGAG)4 GQ to reach a 2 : 1 H2 TCPPSpm4 : GQ ratio T 1/2 higher than 80 °C was also observed confirming the presence of higher-ordered GQ structures.